Meningkatkan Motivasi Belajar dengan Metode Pembelajaran Kooperatif Melalui Model Jigsaw pada Materi Beriman Kristiani di Kelas IX SMP Negeri 8 Ngabang, Landak - Kristina Meni; Nerita Setianingtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The application of the cooperative learning model is the result of reflection on the educational process that has been going on so far. Schools tend to be arenas of competition. Starting from the beginning of their education at school, a child learns in a competitive atmosphere and must fight hard to win the competition to move up a class or pass the exam. According to Anita Lie (2002:24) one of the philosophies underlying the competitive education pattern is Darwin's theory of evolution, which states that the strong will win and survive in life. The principle of survival of the fittest is often reflected in education in schools. Negatively, the competitive learning model will only give birth to a spirit of individualism in students. Based on the background of the problem as above, we compiled this Classroom Action Research with the title "Increasing Learning Motivation with the Cooperative Learning Method through the Jigsaw Method on Christian Faith Material in Class IX of SMP Negeri 8 Ngabang, Landak". The application of the Jigsaw Model cooperative learning method can make Catholic Religion and Character lessons that seem boring more enjoyable.